Implementation of Augmented Reality (AR) as A Teaching Media in English Language Learning in Elementary School - Shaumiwaty Shaumiwaty; Endang Fatmawati; Heni Novita Sari; Yoiceta Vanda; Herman Herman (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2022)
This study discussed the application of augmented reality as a medium of learning in English subjects in elementary schools. This study used multimodal analysis. The theory used is Multimodal by Kress and Leeuwen. The object of this research was a teacher who teaches English subjects in elementary schools. The location of this research is at one Elementary school in Medan city. In data collection used nonverbal data in the form of images, assisted by recording techniques, with the method of listening. The data collection instrument used a questionnaire, and an interview sheet. The results of this study are teachers are able to use Augmented Reality-based learning media in learning English well. Hence, there is an increase in student learning outcomes in English subjects after using Augmented Reality-based learning media. Based on the data obtained, it can be concluded that there is an increase in student learning outcomes before and after use which is obtained through the results of the pre-test and post-test, and teachers and students feel more fun in learning seen from the results of filling out the questionnaire which is carried out to obtain a score that is categorized as very good